Attitudes of members of the public to mass casualty incidents in Singapore - Yeong Yao Qun; Tan Elizabeth Ming Jing; John Low; Sean Kong Yao Zu; Aishwini Ponampalam; R. Ponampalam (Journal of Emergency Management, 2026)
Introduction: Disasters result in mass casualties at short notice and stress healthcare systems. Research shows the critical potential role laypersons can play by providing time-critical intervention on-scene, reducing mortality and morbidity. Our study aims to discover the attitudes of members of the public (MOP) to responding to mass casualty incidents (MCIs) in Singapore.Methods: MOP were invited to participate in a pilot course aimed at educating them on the principles of disaster response and basic interventions for MCIs. Respondents were invited to answer a questionnaire that aimed to explore knowledge, willingness, attitudes, and readiness toward disaster response. This was scored on a Likert scale of 5. Descriptive statistics were performed with thematic analysis for narrative data.Results: A total of 29 participants responded. 69 percent were female. The median age was 50. 65.5 percent had no previous experience with first aid, and none had experience with MCIs. Understanding of MCIs was poor (1.42/5). Respondents were most willing to assist in conventional disasters. Competency and altruism were the most important motivators, while compensation was the least. There is overall appreciation that Singapore is at risk of disasters, although most did not have personal contingency plans in place for disaster situations.Discussion: This study shows that while MOP are willing, the knowledge or experience to respond to MCIs is lacking. More research is needed to understand the attitudes and willingness of MOP in responding to MCIs. This will help identify gaps and plan interventions to enable contributions in times of disaster through volunteerism.